Freedom in Okky Madasari's Bound 2014: A Sociological Perspective - Imroah, Zulfa Happy (2016)
The major problem in this study is to analyze freedom in Bound novel by Okky Madasari. The objective of the study is to analyze Okky Madasari's Bound novelbased on the structural elements and based on the sociological perspective. The researcher uses qualitative research. The primary data source of the study is Bound novel by Okky Madasari, the secondary data source of the study is books, internet about freedom theory and sociological perspective, and the other sources that support the analysis. The method of the data collection is library research. The researcher has the following conclusions. The study shows that the problem of the major character is the struggle to get freedom in his life from those of the mind and body, from restraints imposed by tradition, family, society and religion, from economic domination and the shackles of authority. Based on the structural analysis there are six components as characters and characterization, theme, plot, setting, point of view and style. Based on the sociological perspective analysis there are five aspects as social aspect, economic aspect, political aspect, cultural aspect, and religious aspect. The last based on the freedom analysis there are two components as positive freedom and negative freedom. Keywords: Bound, freedom, sociological.